The Gut Microbiome and Sex Hormone-Related Diseases - He, Song; Li, Hao; Yu, Zehui; Zhang, Faming; Liang, Sicheng; Liu, Hang; Chen, Hongwei; Lü, MuHan (Frontiers in Microbiology, 2021)
The role of the gut microbiome has been a hot topic in recent years. One aim of this review is to shed light on the cross-talk between sex hormones and the gut microbiome. Researchers have observed a sex bias of the composition of the gut microbiome in mice and have proved that sex differences influence the composition of the gut microbiome, although the influence is usually obscured by genetic variations. Via cell studies, animal studies and some observational studies in humans, researchers have confirmed that the gut microbiome can be shaped by the hormonal environment. On the other hand, some theories suggest that the gut microbiota regulates the levels of sex hormones via interactions among its metabolites, the immune system, chronic inflammation and some nerve-endocrine axes, such as the gut-brain axis. In addition, bidirectional interactions between the microbiome and the hormonal system have also been observed, and the mechanisms of these interactions are being explored. We further describe the role of the gut microbiome in sex hormone-related diseases, such as ovarian cancer, postmenopausal osteoporosis, polycystic ovary syndrome, and type 1 diabetes. Among these diseases, postmenopausal osteoporosis is described in detail. Finally, we discuss the treatments of these diseases and the application prospects of microbial intervention.